Prevalensi Bakteriuria Asimtomatik pada Ibu Hamil di Daerah Pesisir - Juminten Saimin; Ashaeryanto Ashaeryanto; Asmarani Asmarani (Halu Oleo University, 2018)
ABSTRACTBackground: Pregnant women more often experience urinary tract infections, especially asymptomatic bacteriuria. Asymptomatic bacteriuria in pregnant women increases the risk of preterm labor, low birth weight, and pyelonephritis.Objectives: This study aimed to determine the prevalence of asymptomatic bacteriuria in pregnant women in coastal areas.Method:This study design was analytic observational with cross sectional method. The research was carried out in the coastal area of Kendari city. The population was pregnant women who performed antenatal care in the working area of Puskesmas Mata, Puskesmas Nambo and Puskesmas Abeli in May-October 2016. Sampling was simple random sampling. Data analysis used Chi square test with significance level <0.05.Result:In this study 268 urine samples were obtained from respondents who performed antenatal care in the coastal area of Kendari City. The highest respondents aged 26-30 years old (42.1%), high school education (49.6%), third trimester (55, 6%) and the entrepreneurial husband (41.8%). Examination of bacteriuria showed positive test with nitrite and leukocytes (24.6%) and positive nitrite and/or leukocytes (30.9%). The highest prevalence of bacteriuria occurs in the third trimester (36.9%). Chi-square test showed a significant difference in the prevalence of bacteriuria according to gestational age (p <0.00).Conclusion: The prevalence of asymptomatic bacteriuria in pregnant women in coastal areas was 30.9%. The highest prevalence occurs in third trimester of pregnancy.Key words :asymptomatic bacteriuria, gestational age, pregnant women